Iptek Bagi Masyarakat: Sumur Resapan Desa Tanjung Gusta untuk Pengendali Banjir - Zulkarnain, Fahrizal (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2017)
The use of infiltration well as a flood controller can also be useful in anticipation of the decrease in the watertable in the dry season. Infiltration well also serves to maintain the ground water level, decrease groundwatercontamination, reduce groundwater degradation, help to overcome the lack of clean water, maintain water balance in thesoil, reduce the stagnant residential areas due to poorly functioning drainage system, and reduce soil erosion in someplaces due to lack of water infiltration into the soil. The water from the infiltration well will lead to a deep soil layer sothat the decrease of the ground water surface will not occur in a short time due to its existence. Community participationin implementing infiltration wells is very functional and will significantly reduce the impact of floods. In general, infiltration wells that can help reduce surface water are those that have a well dimension of 2 x 2 x 2 meters, thusaccommodating the water volume of  8 m3 expected to be impregnated into the ground as soon as possible to cope with flooding